2021
DOI: 10.3748/wjg.v27.i17.1943
|View full text |Cite
|
Sign up to set email alerts
|

BRCA mutated pancreatic cancer: A change is coming

Abstract: Pancreatic cancer remains a leading cause of cancer-related death with few available therapies for advanced disease. Recently, patients with germline BRCA mutations have received increased attention due to advances in the management of BRCA mutated ovarian and breast tumors. Germline BRCA mutations significantly increase risk of developing pancreatic cancer and can be found in up to 8% of patients with sporadic pancreatic cancer. In patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 82 publications
(125 reference statements)
1
50
0
Order By: Relevance
“…BRCA1 mutations in FPC have not been reported as well as BRCA2 , but with a lower frequency [ 35 ]. Here, we found a higher percentage of BRCA1 mutations in 10.7% of patients, not in line with data reported (1.2–2.6%) [ 26 , 27 , 36 ]. Moreover, in a retrospective study on FPC families, BRCA1 mutations occur in 9.5% [ 28 ], this could be due to a different ethnic distribution.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…BRCA1 mutations in FPC have not been reported as well as BRCA2 , but with a lower frequency [ 35 ]. Here, we found a higher percentage of BRCA1 mutations in 10.7% of patients, not in line with data reported (1.2–2.6%) [ 26 , 27 , 36 ]. Moreover, in a retrospective study on FPC families, BRCA1 mutations occur in 9.5% [ 28 ], this could be due to a different ethnic distribution.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the mutation rate in HBOC and LS, was higher (28.6%) than data previously found, showing the frequency of mutation in BRCA1/2 genes be up to 17% in HBOC and in MMR genes up to 12% in LS [ 26 ]. The difference in mutation prevalence could be influenced by the selection of the patients included.…”
Section: Discussionmentioning
confidence: 97%
“…A prospective study of 5,149 females with BRCA1 or BRCA2 carriers showed a significant 2.4-fold increase in the incidence of pancreatic cancer and the increase in the incidence of pancreatic cancer was similar for BRCA1 (SIR = 2.55) and BRCA2 (SIR = 2.13) [ 85 ]. Among unselected pancreatic cancer patient cohorts, multiple studies have shown to estimate the incidence of germline BRCA mutations ranged from 0.7–5.7% for BRCA2 and 0.3–2.3% for BRCA1 [ 86 ]. Of the 145 Jewish pancreatic adenocarcinoma patients, 8 patients (5.5%) were found to have BRCA mutations, 6 patients (4.1%) carried a BRCA2 mutation (6174delT) and 2 patients (1.3%) carried a BRCA1 mutation (185delAG and 5382insC) [ 87 ].…”
Section: Differences Of Other Brca -Related Cancers Risks By Brca1/2 Mutationmentioning
confidence: 99%
“…Besides the analysis of consequences and biotypes, we were interested in evaluating whether clinically relevant and therapeutically meaningful gene variants are properly reflected by ev- and cfDNA analysis in comparison to tumor biopsy samples. To this end, the incidence of germline pathogenic BRCA variants in pancreatic cancer was described with a prevalence ranging from 0.3–2.3% for BRCA1 and 0.7–5.7% for BRCA2 [ 47 ]. BRCA variants that impair protein function are known to sensitize tumors to platinum analogs and inhibition with the poly(adenosine diphosphate ribose) polymerase (PARP) inhibitor olaparib [ 48 ].…”
Section: Resultsmentioning
confidence: 99%